Rumah Makan Mkitchen: a beacon of hope - Ahmad Puzi, Asmarani (Society for the Promotion of Sustainable Development Goals, 2024)
The unprecedented threat of Covid 19 has led to global turmoil of 2020, an extraordinary venture named Rumah Mkitchen emerged as a beacon of hope and solidarity.. Founded in a year marked by the COVID-19 pandemic, a time when businesses shuttered and countless individuals faced unemployment and hunger while Rumah Makan Mkitchen embarked on a noble mission. As businesses closed and the economy staggered the pioneers of Mkitchen saw an urgent need to act The recognition that among the university community, many students and staff members were silently battling hunger and financial despair, their woes amplified by the pandemic. The efforts were extended to the nearby underprivileged communities.. The strategy was not just any ordinary eatery. It was a charity kitchen with a vision to combat food insecurity among the university's students and staff particularly targeting the low income., poor, and needy within the community. The inception of Rumah Makan Mkitchen was driven by a dual purpose to provide free meals to those hit hardest by the pandemic and to create 3E's which are employment, empowerment and entrepreneurial opportunities with a new digital business in the food industry for the marginalized. Both main purposes emerged in transforming the low-income, poor and needy into financial independence and breaking the cycle of poverty. The challenge on the implementation was monumental. The effects of Rumah Makan Mkitchen beyond just feeding people when it encourages resilience and a sense of community, motivating others to support a more important cause. With an eye towards the future, Rumah Makan Mkitchen is committed to being a lighthouse of opportunity and hope shedding light on a road that others might take to cultivate empathy and harmony. Overall, Rumah Makan Mkitchen serves as a shinning example of how local initiative can contribute to achieving broader global goals such as the SDGs. Through its holistic approach to addressing poverty and its commitment to empowering marginalized communities. Rumah Makan Mkitchen demonstrates the transformative power of community-driven action in creating a more equitable and sustainable future.